(untitled) (The Peerian Journal, 2025)
This article analyzes how female characters in the works of one of the prominent figures of 21st-century English literature — Anglo-Japanese writer Kazuo Ishiguro — reflect the complex processes of intercultural identity formation. Using examples from the novels “The Remains of the Day” (1989), “An Artist of the Floating World” (1986), “Never Let Me Go” (2005), and “Klara and the Sun” (2021), the study explores the traits typical of English society such as self-control duty and emotional suppression as well as Japanese values like loyalty and familial obligation through the lens of female characters. The analysis highlights how these women become symbolic intersections of cultural dialogue